Comparative study of heterotopic bone induction using porcine bone morphogenetic proteins delivered into the rodent subcutaneous space with allogeneic and xenogeneic collagen carriers - Duneas, Nicolaas (University of Pretoria, 2013)
Dissertation (MChD)--University of Pretoria, 2009.